The Impact of Websites on Information Literacy and Digital Skills of Rural Communities in Sinjai Regency - Miftahul Janna Awaliyah; Dyah Darma Andayani; Abdul Wahid (Information Technology Education Journal, 2025)
This study aims to analyze the impact of village website utilization on information literacy and digital skills of rural communities in Sinjai Regency. The research was conducted in three villages Pasirmarannu, Panaikang, and Tongke-Tongke that already operate active village websites. Using a quantitative approach and the Technology Acceptance Model (TAM) as the theoretical framework, data were collected through digital questionnaires administered to 100 respondents selected using purposive sampling. The findings reveal that the village websites have a significant positive effect on improving both information literacy and digital skills. Multiple linear regression analysis shows that the website impact variable has a significant relationship with information literacy (Y1) and digital skills (Y2), with coefficients of 0.172 and 0.189, respectively. Furthermore, the descriptive analysis indicates that rural communities benefit from easier access to information, better understanding of technology, and increased administrative efficiency through the use of village websites. The study concludes that the websites serve as an effective tool to support digital transformation in rural areas, particularly in enhancing information literacy and digital skills. It recommends strengthening digital infrastructure, providing community training, and optimizing website management to ensure that the benefits are maximized and accessible to all members of society.